WORLD EXPERIENCE OF FIGHTING THE SMALLPOX VIRUS - Мироник, Олена; Ковальчук, Ангеліна; Пархоменко, Ірина; Берчук, Анастасія (Modern engineering and innovative technologies, 2023)
This article examines the distribution of the smallpox virus in the world, the latest cases of this disease among mankind, how it manifests itself when it enters the human body, as well as means of combating this particularly dangerous infection